Neural Responses to Musical Rhythm in Chinese Children With Reading Difficulties - Chiang, Chun-Han; Hämäläinen, Jarmo; Xu, Weiyong; Wang, Hsiao-Lan (Frontiers in Psychology, 2020)
The perception of the musical rhythm has been suggested as one of the predicting factors for reading abilities. Several studies have demonstrated that children with reading difficulties (RD) show reduced neural sensitivity in musical rhythm perception. Despite this prior evidence, the association between music and reading in Chinese is still controversial. In the present study, we sought to answer the question of whether the musical rhythm perception of Chinese children with RD is intact or not, providing further clues on how reading and music might be interlinked across languages. Oddball paradigm was adapted for testing the difference of musical rhythm perception, including predictable and unpredictable omission, in elementary school children with RD and typically developing age-controlled children with magnetoencephalography (MEG). We used the cluster-based permutation tests to examine the statistical difference in neural responses. The event-related field (ERF) components, mismatch negativity (MMNm) and P3a(m), were elicited by the rhythmical patterns with omitted strong beats. Specifically, differential P3a(m) components were found smaller in children with RD when comparing the rhythmical patterns between predictable and unpredicted omission patterns. The results showed that brain responses to the omission in the strong beat of an unpredicted rhythmic pattern were significantly smaller in Chinese children with RD. This indicated that children with RD may be impaired in the auditory sensitivity of rhythmic beats. This also suggests that children with reading difficulties may have atypical neural representations of rhythm that could be one of the underlying factors in dysfluent reading development.